Intracerebral Hematoma Following Evacuation of Chronic Subdural Hematoma: A Case Report and Review of Literature - Bansal, Sumit; Mahapatra, Ashok K. (Indian Journal of Neurotrauma, 2017)
Intracerebral hematoma is an unusual complication following surgical evacuation of chronic subdural hematoma. We report a case of 61-year-old patient operated at our department for a right-sided chronic subdural hematoma (CSDH), who presented with mild headache and left hemiparesis (4/5, Medical Research Council [MRC] grade). Postoperatively, the patient developed a small hematoma in ipsilateral frontal lobe. Serial computed tomography (CT) of the head showed progressive increase in size of hematoma with development of motor dysphasia. Frontal hematoma was evacuated by craniotomy and the patient improved in motor dysphasia. We emphasize the rarity of this complication and discuss the pathogenesis as well as management of this condition.
Keywords: chronic subdural hematoma; intracerebral hematoma; surgery; good outcome